Mutations at a single codon in Mad homology 2 domain of SMAD4 cause Myhre syndrome - Le Goff, Carine; Mahaut, Clémentine; Abhyankar, Avinash; Le Goff, Wilfried; Serre, Valérie; Afenjar, Alexandra; Destrée, Anne; di Rocco, Maja; Héron, Delphine; Jacquemont, Sébastien; Marlin, Sandrine; Simon, Marleen; et al. (Nature genetics, 2012)
Valérie Cormier-Daire and colleagues report the identification of mutations in SMAD4 that cause Myhre syndrome, a developmental disorder characterized by short stature, short hands and feet, facial dysmorphism, muscular hypertrophy, deafness and cognitive delay. All of the mutations alter a single codon in the Mad Homology 2 domain of SMAD4. Myhre syndrome (MIM 139210) is a developmental disorder characterized by short stature, short hands and feet, facial dysmorphism, muscular hypertrophy, deafness and cognitive delay. Using exome sequencing of individuals with Myhre syndrome, we identified SMAD4 as a candidate gene that contributes to this syndrome on the basis of its pivotal role in the bone morphogenetic pathway (BMP) and transforming growth factor (TGF)-β signaling. We identified three distinct heterozygous missense SMAD4 mutations affecting the codon for Ile500 in 11 individuals with Myhre syndrome. All three mutations are located in the region of SMAD4 encoding the Mad homology 2 (MH2) domain near the site of monoubiquitination at Lys519, and we found a defect in SMAD4 ubiquitination in fibroblasts from affected individuals. We also observed decreased expression of downstream TGF-β target genes, supporting the idea of impaired TGF-β–mediated transcriptional control in individuals with Myhre syndrome.